Kawasaki disease: abnormal initial echocardiogram is associated with resistance to IV Ig and development of coronary artery lesions - Dima Chbeir; Jean Gaschignard; Ronan Bonnefoy; Constance Beyler; Isabelle Melki; Albert Faye; Ulrich Meinzer (BMC, 2018)
Abstract Background Kawasaki disease (KD) is an acute febrile systemic vasculitis that affects small and medium blood vessels. Intensified treatments for the most severely affected patients have been proposed recently, and the early identification of KD patients at high risk for coronary artery aneurysms (CAA) is crucial. However, the risk scoring systems developed in Japan have not been validated in European populations, and little data is available concerning the link between initial echocardiogram findings other than high z-scores and cardiac prognosis. Methods In order to investigate whether the presence of any abnormalities, other than high z-scores in first echocardiogram, are associated with resistance to IV immunoglobulins and/or subsequent development of CAA, we retrospectively analyzed data from children diagnosed with KD between 2006 and 2016 at a tertiary Hospital in Paris, France. Results A total of 157 children were included. The initial echocardiogram was performed after a median of 7 days of fever and was abnormal in 48 cases (31%). The initial presence of any echocardiographic abnormality (coronary artery dilatation, CAA, pericardial effusion, perivascular brightness of the coronary arteries, left-ventricular dysfunction and mitral insufficiency) was strongly associated with resistance to intravenous immunoglobulin (p = 0.005) and development of coronary artery lesions within the first 6 weeks of disease (p = 0.01). All patients (n = 7) with persistent coronary abnormalities at 1 year already had an abnormal initial echocardiogram. Severity scoring systems from Japan had low sensitivity (0-33%) and low specificity (71-82%) for predicting immunoglobulin resistance or cardiac involvement. Conclusions In European populations with mixed ethnic backgrounds, the presence of any abnormalities at the initial echocardiogram may contribute to early identification of patients with severe disease.